Application of Different Kinds of Approximation in Signals Restoration - Стрелковська, Ірина Вікторівна; Стрелковська, І. В.; Стрелковская, Ирина Викторовна; Strelkovska, Iryna V.; Lysiuk, Olena; Паскаленко, Станіслав; Paskalenko, Stanislav (My University, 2015)
It is proposed the method of continuous signals restoration by different kinds of approximation: Lagrange polynomial, Kotelnikov interpolation series, linear and cubic splines, Haar wavelet and Kotelnikov-Shannon wavelet. The minimum value of mean-square deviation is used as a criterion. The program witch allow to define optimal method of different class of signals restoration is composed.
Strelkovska I. Application of Different Kinds of Approximation in Signals Restoration / I. Strelkovska, O. Lysiuk, S. Paskalenko //Second International Scientific-Practical Conference Problems of Infocommunications Science and Technology (PIC S&T), 13-15 Oct. 2015. – Kharkiv, Ukraine. – 2015. – 4 с.
Keywords: restoration; signal; approximation; Kotelnikov series; spline functions; wavelet functions; cubic spline; deviation; software product; mean-square deviation; Research Subject Categories::TECHNOLOGY